Analisis Kosmologi Pola Tiga dalam Tradisi Nyeupah pada Masyarakat Sunda - Ahda Yunia Sekar (Gelar : Jurnal Seni Budaya, 2021)
Nyeupah is a term in Sundanese society which means chewing betel leaves. Nyeupah itself has other terms such as nyirih for the Java area and Nginang for the Sumatra area. Consuming betel leaf has been done by our ancestors since the middle of 15th century, where the Chinese, Indians, Persians and Europeans had made transactions for herbs and spices in Nusantara. The Nyeupah tradition in Sundanese society has long existed and it is proved by the existence of Jangjawokan regarding Nyeupah. Jangjawokan is a Sundanese poem which can be interpreted as containing archaic or ajimantra. This article has been written to analyze the Nyeupah tradition in Sundanese society with a three-pattern cosmological approach to be able to give deeper meaning dealing with this tradition.